52 Functional Outcomes and Return to Sport Following Anterior Cruciate Ligament Reconstruction in Recreational Athletes: A Systematic Review. (19th August 2022) - Brzeszczyński, Filip; Forsyth, Kirsty; McLelland, Colin; McDonald, Donnie; Lawson, Graham; Hamilton, David
Abstract: Introduction: Outcomes of anterior cruciate ligament reconstruction (ACLR) are well reported in athletic populations, however surprisingly little information is available for outcomes in the recreational athletes that make up the majority of cases. The aim was therefore to assess post-operative outcome and return-to-sport in recreational athletes following ACLR. Method: A systematic search was conducted in Ovid MEDLINE, CINAHL, AMED and the grey literature according to the PRISMA guidelines. Studies involving a clear definition of recreational athletes who underwent ACLR and recorded postoperative outcomes were included. Publication quality was assessed using Newcastle-Ottawa Scale. Results: 107 studies were identified, 19 full-text records reviewed and 13 included, reflecting 1342 patients with an average age of 31.7 (SD 9.8). Mean follow-up was 43.6-months (SD 42.8). Functional activity change was reported in 92% (12/13) papers. Functional outcome was assessed with the Tegner activity score in seven studies, with 43% (3/7) reporting a post-operative improvement. The Lyshom score was used in five, of which, 60% (3/5) showed post-operative improvement, 20% (1/5) showed no difference and 20% (1/5) showed a decrease. 69% (9/13) studies reported return-to-sport, with a mean rate of 55% (S.D. 19.2) at a mean follow-up of 32-months (SD. 34.8). Reported return-to-sports rate increased with length of follow-up. Conclusions: Approximately only 50% of recreational athletes increase activity level and return-to-sport following ACLR. There is wide variation in return-to-sports timeframes reported, and the link between return-rate and post-operative timeframe suggests that longer follow-up periods may be required to accurately capture return-to-sport rates in recreational athletes.